Las plantas que nos unen (2020)
This degree project aims to create a development model where trade and housing can coexist properly in the city of Bogota because the project is developed around the market Plaza Samper Mendoza, which proposes a revitalization to generate a multi-family housing development having the market as its center. This project is committed to breaking the socioeconomic barriers through the plants, its different inhabitants and the character of the place.